Insecticidal Activity of Microencapsulated Vip3Ag4 protein in Bacillus megaterium - Palma, Leopoldo (2023)
Bacillus thuringiensis (Bt) produces, during its vegetative growth, some insecticidal proteins that are secreted and diluted into the culture medium. These proteins are commonly known as vegetative insecticidal proteins (Vips), and include binary Vpb/Vpa proteins (formerly known as Vip1/Vip2) with coleopteran activity; Vip (formerly Vip3) with activity against lepidopterans; and Vpb4 proteins (formerly Vip4), also with coleopteran activity. Vip proteins are highly toxic to different species of lepidopteran pests; however, the difficulty in producing them in a concentrated form has not allowed their development as formulated biopesticides, and they are relegated to only being produced in transgenic crops. In this work, we demonstrated that the gene encoding the Vip protein Vip3Ag4 could be successfully expressed in an asporogenic strain of Bacillus megaterium using (D)-xylose as a low-cost inductor. Under certain conditions (37 °C and induction with 0.5% w/v xylose), active Vip3Ag4 protein was primarily produced in soluble form, remaining encapsulated within the cell wall of B. megaterium. After treatment with lugol (1% for 4 h), induced cells were completely killed (fixed) but maintained the functional Vip3Ag4 protein, which resulted in above 95% mortality against first-instar larvae of Chrysodeixis chalcites, Helicoverpa armigera, Spodoptera exigua, S. frugiperda, S. littoralis and Trichoplusia ni. The fact that the recombinant Vip3Ag4 protein was successfully produced in a soluble and an active form in this bacterium (with a low-cost inductor) suggests that B. megaterium is one of the hosts of choice for the production of sprayable formulations in “killed-microbial pesticides”, based on Vip3 proteins from Bt.